Surface Engineering of Dental Implants: Techniques, Mechanisms, and Clinical Considerations - Eko Budiyanto; Lukito Dwi Yuono (Asian Journal of Mechanical Engineering, 2025)
Dental implants have emerged as one of the most effective and widely accepted solutions for replacing missing natural teeth in modern dentistry. The long-term success or potential failure of dental implants is influenced by a range of local and systemic factors. Among these, the surface characteristics of the implant play a pivotal role in the initial biological response following implantation. In particular, surface roughness has garnered significant interest in recent years due to its ability to enhance the interaction between the implant and the surrounding bone tissue. To promote faster and more effective osseointegration, the direct structural and functional connection between living bone and the surface of the implant, numerous surface modification techniques have been explored. These include mechanical, chemical, and physical treatments, often utilizing various materials designed to improve biocompatibility and promote early bone healing. While a growing body of research suggests that such surface treatments can significantly accelerate healing, particularly in the initial stages following implant placement, clinical decision-making must still be guided by both the available scientific evidence and the specific needs of each patient case. This review article aims to synthesize current knowledge regarding the surface treatment of dental implants. By critically analyzing findings from various experimental and clinical studies, it provides insights into the advantages and limitations of different surface modification techniques currently in use. The goal is to assist clinicians and researchers in selecting appropriate implant systems based on evidence-based outcomes and clinical applicability.